Here's the question you clicked on:
zakeyadorsey
Solve log7 (x – 8) – log7 3 = log7 21
Try to show you work :) Whenever you stop i will help ..
Nope. Show your work step by step to see which part is hard ?
no this is where im stuck at
hmm,Actually thats wrong and that mean that the previous step which lead to this was wrong..
Btw : here is hint \[Logx=Logy\] x=y
well all i did was put log7(x-8)over log7(3)=log7 21 then just took off the log7
Its not \[ \Large \frac{Log_{7}(x-8)}{Log_{7}(3)}\] It is : \[ \Large Log_{7} \frac{(x-8)}{(3)}\]
So now u have \[ \Large \frac{x-8}{3}=21\] 63=x-8 x=71
ok but were did you get 63
ooh neverminod i got it thanks
lets look over some basic properties such as log(a/b) = log a - log b and log(a*b)= log a + log b and if logx= log y then x=y just because everything is in the base of 7 we could use these properties as well so therefore from your question log7 (x – 8) – log7 3 = log7 21 let us use the first property on the left side and get log7((x-8)/3) = log 7 21and now let us use the third property to obtain (x-8)/3 = 21 and that will get us x-8 = 63 and now solve for x to obtain x = 71 :)
thanks for the help everyone.I really needed it